PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN ASING TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Asa Idilla Latifah; Nidia Anggreni Das; Witra Maison (Jurnal Bina Bangsa Ekonomika, 2024)
This research was conducted to determine the influence of audit quality (X1) on earnings management (Y), the audit committee (X2) on earnings management (Y) and the simultaneous influence of audit quality (X1) and the audit committee (X2) on earnings management (Y). The research results show that Audit Quality (X1) has an effect on Earnings Management (Y). This result is proven by the calculated t value of |2.177| ≥ |1.99300| and significance value 0.033 ≤ 0.05. For the Audit Committee (X2) it has no effect on Earnings Management (Y). This result is proven by the tcount value of |1.579| ≤ 1.99300 and significance value 0.119 ≥ 0.05. After that, Audit Quality (X1) and Audit Committee (X2) do not simultaneously influence Profit Management (Y). This result is proven by the Fcount value of |2.717| ≤ 2.859 and significance value 0.073 ≥ 0.05